How Do The Main Negative Emotions Affect People's Political Decision Process? : “Fear, Anxiety And Anger - Kevser Hülya Akdemir (Akademik İncelemeler Dergisi)
In the post-modern era, the mobilization of previously large masses has been replaced by micro-groups dominated by new and distinct identities. As a result, the analysis and predictability of electorate behavior have decreased. The political decision-making processes of individuals have therefore been subjected to detailed analyzes. Emotions have become a significant subject of political psychology in terms of their effects on the political decision-making process of individuals. Emotions have also become an important topic in political psychology. Researches revealed that emotions have important effects on thoughts and decision-making processes. In this context, the article primarily aims to draw a rational framework on this subject by including modern “emotion” definitions and the impacts of people’s emotions on political decisions. Afterward, the article investigated the effect of negative emotions on political decision-making. In this context, anxiety, fear and anger are emphasized by using a descriptive approach. The article argues that negative emotions that are anxiety, fear, and anger, in particular, have positive contributions to the political decision-making process of individuals.